Prevention of Spinal Anesthesia-induced Hypotension During Cesarean Delivery by 5-Hydroxytryptamine-3 Receptor Antagonists: A Systematic Review and Meta-analysis and Meta-regression. Issue 2 (June 2017) - Heesen, M.; Klimek, M.; Hoeks, S.E.; Rossaint, R.
Abstract : ( Anesth Analg. 2016;123(4):977–988) Hypotension is a common complication affecting obstetric patients receiving spinal anesthesia, and can lead to nausea and vomiting, altered consciousness, and increased risk of aspiration. As 5-hydroxytryptamine (5-HT3, serotonin) receptors are involved in the mechanism, studies have evaluated 5-HT3 receptor antagonists for their potential to prevent spinal anesthesia-induced hypotension. The authors of the present meta-analysis reviewed the effect of 5-HT3 receptor antagonists on the frequency of hypotension in patients undergoing spinal anesthesia.